A treasury of virtues : sayings, sermons and teachings of ʻAlī al-Qāḍī al-Quḍā'ī : with the one hundred proverbs attributed to al-Jāhiẓ - ʻAlī ibn Abī Ṭālib, Caliph, approximately 600-661 (Library of Arabic literature., 2013)
This book is a collection by the Fatimid Shafi'i judge al-Quda'i (d. 454 H/1062 AD) of sayings, sermons, and teachings attributed to 'Ali ibn Abi Talib (d. 40 H/661 AD). 'Ali was the cousin and son-in-law of the Prophet Muhammad, the first Shia Imam and the fourth Sunni Caliph. An acknowledged master of Arabic eloquence and a sage of Islamic wisdom, Ali was renowned for his words, which were collected, quoted, and studied over the centuries, and extensively anthologized, excerpted, and interpreted. Included here are aphorisms, proverbs, sermons, speeches, homilies, prayers, letters, dialogues, and verse, all of which provide instruction on how to be a morally upstanding human being.